2007
DOI: 10.1007/s10646-007-0166-9
|View full text |Cite
|
Sign up to set email alerts
|

The effect of in situ cadmium contamination on some biomarkers in Cerastoderma glaucum

Abstract: The present study was designed to detect in situ effects of cadmium on marine organisms Cerastoderma glaucum from the gulf of Gabès (Tunisia). Six sampling stations were chosen: one site, relatively far from known local source of pollution, was considered as uncontaminated site and five sites clearly exposed to anthropogenic impact. Metallothionein like protein (MTLP) and sub-cellular metal partitioning were measured in cockles (C. glaucum) gills and digestive gland. Various biomarkers were also measured, incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 38 publications
2
18
0
Order By: Relevance
“…Additionally, they may be affected also by metals, although the effect may be either metal-or species-dependent since, while no effect was observed in mussels exposed to Cu (Regoli and Principato 1995), Machreki-Ajmi et al (2008) and Bonacci et al (2008) observed cholinesterase inhibition in clams when exposed to Cd.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, they may be affected also by metals, although the effect may be either metal-or species-dependent since, while no effect was observed in mussels exposed to Cu (Regoli and Principato 1995), Machreki-Ajmi et al (2008) and Bonacci et al (2008) observed cholinesterase inhibition in clams when exposed to Cd.…”
Section: Discussionmentioning
confidence: 99%
“…When they are exposed to Cd in company with other metals, Cd values are highest in the digestive gland (Martín-Díaz et al 2005). Cd accumulation was also found to be higher in the digestive gland of the cockle Cerastoderma glaucum from Gabès Gulf than in the gills (Machreki-Ajmi et al 2008). …”
Section: Metal Concentrations In Sediments and Crab Organsmentioning
confidence: 92%
“…Crude phosphate treatments, chemical industries, tanneries, and plastics plants release pollutionloaded effluents into the marine environment; these pollutants include toxic metals, which are washed back by tides to the littoral area (Louati et al 2001, Banni et al 2005, Zaghden et al 2005, MachrekiAjmi et al 2008, Smaoui-Damak et al 2009). Cd from phosphate plants is one of the main contaminants in the Gabès area , SmaouiDamak et al 2003, Machreki-Ajmi et al 2008. Samples were collected from: (1) Bizerte (BIZ) Lagoon, and (2) Gargour (GAR), in Gabès Gulf, both of which areas receive urban, industrial and agricultural pollution, and (3) Teboulba (TEB), with no main contamination sources and considered a reference site in many field studies (Banni et al 2007, Jebali et al 2007, Bouraoui et al 2010.…”
Section: Sampling Sites Animals and Handlingmentioning
confidence: 99%
See 1 more Smart Citation
“…and Cd 2? inhibit algal b-D-galactosidase (Peterson and Stauber 1996) and algal b-glucosidase (Obst 1988), as well as fish phosphatases (El Demerdash and Elagamy 1999;Gill et al 1991) and mollusc acetylcholinesterase (Machreki-Ajmi et al 2008). The activities of glucose-6-phosphate dehydrogenase (Kong and Chen 1995) and phosphatases (Rai et al 1998) were decreased by Al 3?…”
Section: Introductionmentioning
confidence: 98%